The Dizang Baojuan in the Performance Context of “Telling Scriptures” in Changshu, Jiangsu - Berezkin, Rostislav Vladimirovič (Journal of Chinese religions, 2020)
This article deals with the modern performance context of the Dizang baojuan in Changshu, Jiangsu province. The local tradition of ritualized storytelling, called “telling scriptures,” makes use of the Bodhisattva Dizang’s narratives presumably derived from the late Qing-dynasty printed edition of the Dizang baojuan. However, in the modern performance context, the stories of Dizang’s reincarnations have been separated according to performance occasions. There are several such occasions, including funerary ritual and memorial days of the “fifth week” (programs of male and female funerary services vary) and village temple festivals, at which Dizang is also worshipped. Still, all variants of the Dizang baojuan preserve the central message of the universal deliverance of the souls of the deceased. The author researches the origins, modification, and current functions of the centuries-old Dizang narratives in the modern storytelling of Changshu. Materials of telling scriptures in Changshu and adjacent areas demonstrate the transformation of the canonical Buddhist subjects in the local vernacular literature and folk ritual, their sinicization and domestication in local cultural milieus. Materials used in this article have been collected by the author in Changshu through interviews with performers and observation of real-life telling scriptures in 2011-2017.